Defining the phenotype associated with microduplication reciprocal to Sotos syndrome microdeletion. Issue 8 (12th May 2014) - Novara, Francesca; Stanzial, Franco; Rossi, Elena; Benedicenti, Francesco; Inzana, Francesca; Di Gregorio, Eleonora; Brusco, Alfredo; Graakjaer, Jesper; Fagerberg, Christina; Belligni, Elga; Silengo, Margherita; Zuffardi, Orsetta; et al.
<x xml:space="preserve">Abstract</x> NSD1 point mutations, submicroscopic deletions and intragenic deletions are the major cause of Sotos syndrome, characterized by pre‐postnatal generalized overgrowth with advanced bone age, learning disability, seizures, distinctive facial phenotype. Reverse clinical phenotype due to 5q35 microduplication encompassing NSD1 gene has been reported so far in 27 cases presenting with delayed bone age, microcephaly, failure to thrive and seizures in some cases, further supporting a gene dosage effect of NSD1 on growth regulation and neurological functions. Here we depict the clinical presentation of three new cases with 5q35 microduplication outlining a novel syndrome characterized by microcephaly, short stature, developmental delay and in some cases delayed bone maturation, without any typical facial or osseous anomalies. © 2014 Wiley Periodicals, Inc.